Expression and DNA methylation of SERK, BBM, LEC2 and WUS genes in in vitro cultures of Boesenbergia rotunda (L.) Mansf. - Karim, Rezaul; Tan, Yew Seong; Singh, Pooja; Khalid, Norzulaani; Harikrishna, Jennifer Ann (Springer, 2018)
The process of somatic embryogenesis and plant regeneration involve changes in gene expression and have been associated with changes in DNA methylation. Here, we report the expression and DNA methylation patterns of SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE (SERK), BABY BOOM (BBM), LEAFY COTYLEDON 2 (LEC2) and WUSCHEL (WUS) in meristematic block of newly emerged shoots from rhizome, embryogenic and non-embryogenic calli, prolonged cell suspension culture, ex vitro leaf, and in vitro leaf of regenerated plants of Boesenbergia rotunda. Among all seven samples, based on qRT-PCR, the highest level of expression of SERK, BBM and LEC2 was in embryogenic callus, while WUS was most highly expressed in meristematic block tissue followed by embryogenic callus. Relatively lower expression was observed in cell suspension culture and watery callus for SERK, LEC2 and WUS and in in vitro leaf for BBM. For gene specific methylation determined by bisulfite sequencing data, embryogenic callus samples had the lowest levels of DNA methylation at CG, CHG and CHH contexts of SERK, LEC2 and WUS. We observed negative correlation between DNA methylation at the CG and CHG contexts and the expression levels of SERK, BBM, LEC2 and WUS. Based on our results, we suggest that relatively higher expression and lower level of DNA methylation of SERK, BBM, LEC2 and WUS are associated with somatic embryogenesis and plant regeneration in B. rotunda.